Hospital-acquired Pneumonia and Ventilator-associated Pneumonia in Children: A Prospective Natural History and Case-Control Study. Issue 8 (August 2020) - Ericson, Jessica E.; McGuire, John; Michaels, Marian G.; Schwarz, Adam; Frenck, Robert; Deville, Jaime G.; Agarwal, Swati; Bressler, Adam M.; Gao, Jamie; Spears, Tracy; Benjamin, Daniel K.; Smith, P. Brian; et al.
Abstract : Background: Clinical trials for antibiotics designed to treat hospital-acquired and ventilator-associated bacterial pneumonias (HABP/VABP) are hampered by making these diagnoses in a way that is acceptable to the United States Food and Drug Administration and consistent with standards of care. We examined laboratory and clinical features that might improve pediatric HABP/VABP trial efficiency by identifying risk factors predisposing children to HABP/VABP and describing the epidemiology of pediatric HABP/VABP. Methods: We prospectively reviewed the electronic medical records of patients <18 years of age admitted to intensive and intermediate care units (ICUs) if they received qualifying respiratory support or were started on antibiotics for a lower respiratory tract infection or undifferentiated sepsis. Subjects were followed until HABP/VABP was diagnosed or they were discharged from the ICU. Clinical, laboratory and imaging data were abstracted using structured chart review. We calculated HABP/VABP incidence and used a stepwise backward selection multivariable model to identify risk factors associated with development of HABP/VABP. Results: A total of 862 neonates, infants and children were evaluated for development of HABP/VABP; 10% (82/800) of those receiving respiratory support and 12% (103/862) overall developed HABP/VABP. Increasing age, shorter height/length, longer ICU length of stay, aspiration risk, blood product transfusion in the prior 7 days and frequent suctioning were associated with increased odds of HABP/VABP. The use of noninvasive ventilation and gastric acid suppression were both associated with decreased odds of HABP/VABP. Conclusions: Food and Drug Administration-defined HABP/VABP occurred in 10%–12% of pediatric patients admitted to ICUs. Risk factors vary by age group. Abstract : Supplemental Digital Content is available in the text.